IMPLEMENTATION OF COMMUNICATIVE APPROACH IN MUHADATSAH LEARNING IN THE DIGITAL ERA - Tampubolon, Muhammad Syafii; Ilahi, Rahmad (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
This study aims to explore the effectiveness of the communicative approach supported by digital technology in muhadatsah learning (Arabic speaking skills) among secondary-level students. The communicative approach was chosen as it addresses the limitations of traditional methods. The research employed a classroom action research method conducted in two cycles, involving tenth-grade students at STIT Madani Yogyakarta. Data were collected through observations, interviews, speaking proficiency tests, and motivation questionnaires. The results indicated a significant improvement in all three aspects of speaking skills, with gains ranging from 25% to 32%. Furthermore, students demonstrated increased confidence and learning motivation following the implementation of interaction-based instruction and the use of digital media, such as conversation applications and online learning platforms. The main challenges identified were limited internet. These findings affirm that the integration of the communicative approach with digital technology fosters more interactive and adaptive learning, in line with the demands of the digital era. Therefore, adequate infrastructure and teacher training are essential for sustainable implementation.